The frequency of mosaic epidural block during labour. The comparison of two kinds of epidural catheters - Lisnyy, I. I.; Chechelnitskiy, O. E.; Emets, V. M. (Pain medicine, 2016)
It is assumed that the design of the epidural catheter may affect the quality of analgesia. Two types of epidural catheters were compared – three and six side perforation holes at the end, and the incidence of incomplete block. Methods: The study included 308 pregnant women who underwent epidural labour analgesia. Group A (Gr. A) included 271 pregnant women in which the epidural catheter with three side holes has been used and group B (Gr. B) included 50 pregnant women in which epidural catheter with six side holes has been used. The incidence of incomplete sensory block to the right or left half of the body was evaluated. Results: It was found that the incidence of incomplete epidural block in patients of Gr. A constituted 31,4 % (n = 81) and in Gr. B – 6 % (n = 3), p = 0.001. There was no statistically significant correlation on age, weight, height and body mass index with incidence of incomplete epidural block. With the development of an incomplete epidural block caesarean section rates did not differ between groups. Conclusions: Using an epidural catheter with six side holes at the end helps to reduce the incidence of incomplete block in epidural analgesia in labour.